2004
DOI: 10.1038/sj.bjc.6601980
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity at 9q33 and hypermethylation of the DBCCR1 gene in oral squamous cell carcinoma

Abstract: The DBCCR1 gene at chromosome 9q33 has been identified as a candidate tumour suppressor, which is frequently targeted by promoter hypermethylation in bladder cancer. Here, we studied the possible involvement of DBCCR1 in the development of oral squamous cell carcinoma. DNA from 34 tumours was examined for loss of heterozygosity (LOH) at three markers surrounding DBCCR1 and for hypermethylation of the DBCCR1 promoter, using methylation-specific PCR and methylation-specific melting-curve analysis. LOH was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…AF027734) was examined by methylation-specific PCR (32). Genomic DNA was treated with sodium bisulfite (33), and primer sequences and conditions for methylation-specific PCR analysis of the DBCCR1 gene promoter were as described (34). Amplification products were resolved in a 2% agarose gel.…”
Section: Methodsmentioning
confidence: 99%
“…AF027734) was examined by methylation-specific PCR (32). Genomic DNA was treated with sodium bisulfite (33), and primer sequences and conditions for methylation-specific PCR analysis of the DBCCR1 gene promoter were as described (34). Amplification products were resolved in a 2% agarose gel.…”
Section: Methodsmentioning
confidence: 99%
“…The DBCCR1 gene has been reported as the gene functionally affected by frequent loss of 9q32-33 in transitional cell carcinomas of the urinary bladder and identified as a candidate tumor suppressor, which is frequently targeted by promoter hypermethylation in bladder cancer (25). It has been reported that LOH at 9q33 and hypermethylation of the DBCCR1 promoter are frequent and possibly early events in oral SCC development (26), however, Gao et al did not perform DNA mapping array analysis. In our whole-genome analysis of LOH, loss of CNA (one copy) was observed in the 9q33 region.…”
Section: Discussionmentioning
confidence: 99%
“…26 MS-PCR was performed using previously described primers and conditions. 15 For MS-MCA, two primer sets were used. The first set (5 0 -GTGGGAATTTGGGAGAGTTTT-3 0 and 5 0 -AA TATAAACCAAACTACTAAAAACCAAATA-3 0 ) amplifies a 100-bp region (including 7 CpG sites) of the DBC1 5 0 CpG island (nt.…”
Section: Promoter Hypermethylation Of Dbc1mentioning
confidence: 99%
“…12 Fine mapping analysis in bladder cancer led to the identification of a putative tumor suppressor gene at 9q33.1, which has been designated as DBC1 (deleted in bladder cancer 1). 13 The 5 0 region of DBC1 contains a CpG island that is aberrantly hypermethylated in approximately 50% of bladder cancer cell lines and tumors, 13,14 40% of oral squamous cell carcinomas, 15 80% of non-small cell lung cancer cell lines, and a proportion of primary non-small cell lung cancer tumors. 16 In bladder cancer, lowdensity DBC1 promoter methylation was shown to occur in an age-related manner in the matched normal tissue, indicating that DBC1 promoter methylation may constitute an early event in carcinogenesis.…”
mentioning
confidence: 99%